Meningkatkan Keterampilan Berbicara Siswa Menggunakan Model Time Token Pembelajaran IPA Kelas V Sekolah Dasar - Rafika Siregar; Atri Widowati; Muhammad Ali (Jurnal Gentala Pendidikan Dasar, 2020)
This study aims to improve students' speaking skills in science learning through time token models in fifth grade students of SDN 43 / IV Jambi City. This research is a classroom action research (CAR) consisting of two cycles, where the data taken is in the form of observation data through observation sheets of students' speaking skills and observation sheets of teacher activities. This research was conducted in 4 stages: planning, implementing, observing and reflecting. During the teaching and learning process learning activities apply the time token learning model. The results of this study indicate the application of the time token model can improve students' speaking skills in natural science subjects. Based on the observation sheet the students' speaking skills showed an increase, with the results of the percentage of students speaking skills by 45% with a fairly good category in the first cycle and 68% with a good category in the second cycle. Based on the findings of the research, it can be concluded that the speaking skills of science learning students in fifth grade students of SDN 43 / IV Jambi City can be improved after applying the time token model.